Silicon fertilization improve yield and quality of rice and pearl millet in cerrado soils - Raquel Castro Salomão Chagas; Takashi Muraoka; Gaspar Henrique Korndörfer; Mônica Sartori de Camargo (Bioscience Journal, 2016)
Although silicon (Si) fertilization in rice (Oryza sativa) plants have already been studied, most of the Brazilian studies have focused on the acidity correction effects of sources and the application rate, but not on Si supply. Moreover, beneficial effects are rarely linked to other Si-accumulation plants such as pearl millet (Pennisetum glaucum), which is extensively grown in low soluble Si of Cerrado soils. The objective of this study was to evaluate the Si sources and application rates on the yield and quality of two commonly cultivated grain crops (rice and pearl millet) in Cerrado soils. The experiments were conducted on two crops (rice and pearl millet) and two soil types (Rhodic Haplustox-LV and Quartzipsamment-RQ) in a completely randomized factorial scheme with four replicates, four Si rates (0; 200; 400, and 800 kg ha-1 Si); and three sources (calcium and magnesium silicate, wollastonite, and silicic acid). All plots received the same quantities of Ca and Mg to equilibrate these levels in both soils. Ca and Mg silicate and wollastonite produced linear increases in soluble Si (0.5 mol L-1 acetic acid), in LV, RQ, and in Si uptake by rice and pearl millet. Increases in shoot dry weight were observed in rice and pearl millet from maximum rates of 542, 550 and 480 kg ha-1 Si in RQ, respectively. Ca and Mg silicate levels were higher than wollastonite in the dry weight of both plants.